ANALISIS PENGARUH KUALITAS PELAYANAN, KEPUASAN PASIEN, DAN LOYALITAS PASIEN TERHADAP IMAGE RUMAH SAKIT DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH LABUANG BAJI TAHUN 2023 - Reza Meifini; Reski Dewi Pratiwi; Adriyana Adevia Nuryadin; Dian Ekawaty (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2025)
Patient satisfaction is an important indicator that must be considered in health services. Based on patient satisfaction data at the Labuang Baji Regional Hospital, it shows that the percentage of patient satisfaction in 2019 was 86.34%, in 2021 it was 70.83% and in 2022 it was 78.46%, it can be seen that the percentage of patient satisfaction at Labuang Baji Hospital has not fulfilled Ministry of Health standard no. 129 of 2008, namely >90%. The purpose of this study was to determine the effect of service quality, patient satisfaction and patient loyalty on the image of the hospital in the inpatient ward of Labuang Baji Hospital in 2023.This research is a quantitative study using the Cross Sectional Study method. This research was conducted in the inpatient room of the Labuang Baji Hospital with a sample of 242 respondents who were determined through a purposive sampling technique. Data collection in this study was obtained through distributing questionnaires and secondary data. Data analysis used SPSS 16.0 to see how many respondents' answers strongly agreed, agreed, disagreed and strongly disagreed, Chi-square test to see the effect of the independent variables on the dependent variable and binary logistic regression test to see the effect of the independent.The results of the study using the chi-square test showed that the quality of service had a value of p = 0.000, because the value of p <α = 0.000 <0.05, it could be concluded that there was an effect of Service Quality on Image, patient satisfaction obtained a value of p = 0.015, because the value of p <α = 0.015 <0.05, it can be concluded that there is an effect of patient satisfaction on Image. Patient loyalty obtained a value of p = 0.011, because the value of p < α = 0.011 < 0.05, it can be concluded that there is an effect of patient loyalty on Image. the hospital is getting better and improving